Tinjauan yuridis terhadap pengaturan terkait pekerja harian lepas - Rakhman Candra Suryaningrat; Mohammad Ghufron Az; Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2021)
Workers / laborers are often extorted by employers with relatively small wages. An employment relationship is basically a relationship between a worker / laborer and an entrepreneur after a work agreement is made. The formulation of the problems discussed in this paper is how to regulate freelance daily workers in Indonesia and how to resolve disputes related to work agreements for casual daily workers in Indonesia. The result of the research on the formulation of the problem is that the regulation regarding freelance workers / laborers is regulated in statutory regulations, in law number 13 of 2003 concerning manpower in Article 56 to Article 59, but there are several articles amended by -Law Number 11 of 2020 concerning work copyright. Settlement of disputes between employers and workers / casual daily laborers can be resolved first by deliberation to reach a consensus in accordance with what has been stipulated in Article 136 paragraph (1) of Law Number 13 of 2003 concerning Manpower, but if deliberation efforts to reach consensus cannot be reached then the management and workers / laborers or trade / labor unions resolve industrial relations disputes.How to cite item: Suryaningrat, R., Ghufron Az, M., Supriyadi, S. (2021). Tinjauan yuridis terhadap pengaturan terkait pekerja harian lepas. Jurnal Cakrawala Hukum, 12(2), 213-222. doi:https://doi.org/10.26905/idjch.v12i2.5813